Enhancing water productivity for poverty alleviation: Role of capitals and institutions in the Ganga Basin - Clement, Floriane; Haileslassie, Amare; Ishaq, S.; Blümmel, Michael; Murty, M.V.R.; Samad, M.; Dey, S.; Das, H.; Khan, M.A. (Cambridge University Press, 2011)
The concept of water productivity (WP) or ‘more crop per drop’ has been revived recently in international water debates. Its application has notably been extended from single crops to mixed farming systems, integrating both crops and livestock, with the wider objective of reducing poverty. Using evidence from the Ganga Basin, India, we discuss the relevance of this concept as a tool to guide interventions for livelihood improvement and poverty alleviation. We argue that WP studies would benefit from greater attention to the role of capitals, inequities and institutions. Firstly, it is crucial to acknowledge the heterogeneity of capitals and capabilities of farmers to make changes in their farming systems and practices and avoid one-fix-all interventions. Identifying pre-existing inequities in water access within and among communities will support better targeting of poor communities. WP interventions can either reinforce or reduce inter-household inequities within communities. We stress the need for assessment of institutional impacts of WP interventions on water access and development.